MENINGKATKAN PERTUMBUHAN EKONOMI SYARI’AH MELALUI DAYA TARIK WISATA HALAL INTERNASIONAL YANG KREATIF - Ramadhan, Muhammad Thoyib; Abdullah Pelu, Muhammad Fariz; Utami, Amanda Tri; Akwila, Friska; Al-Fathan, Danis Zhulfan (Taksasila Edukasi Insani, 2024)
The development of international tourism plays an important role in increasing the attractiveness of halal tourist destinations in Indonesia. Through sectors such as art, culture, technology, and creative industries, the competitiveness of halal tourism can be strengthened with innovations that comply with sharia principles. Creative products and services, such as Muslim fashion, Islamic art-based crafts, and sharia technology, are the main attraction for international Muslim tourists. Indonesia, with its rich culture and nature, has a great opportunity to develop a competitive halal tourism destination in the global market. Even so, challenges such as the lack of synergy between the creative industry and tourism, as well as limited infrastructure, are still obstacles that need to be overcome. Collaboration between the government, the private sector, and the creative community is crucial in creating a sustainable halal tourism ecosystem. This step can increase Indonesia's global competitiveness and support inclusive national economic growth.Keywords : destinasi, ekonomi syri’ah, inovasi, sinergi, wisata halal